The Influence of Thought Stopping Therapy and Family Psychoeducation Toward Anxiety Client Who Undergo Hemodialysis in DR. Achmad Mochtar Hospital - Yade Kurnia Saria; Budi Anna Keliat; Reni Dayati (Faculty of Nursing, Universitas Andalas, 2018)
Background: Clients hemodialysis who were hospitalized around 43.1% experienced anxiety conditions. This is caused by the Client renal failure undergoing hemodialysis, takes 12-15 hours of dialysis every week, or at least 3-4 hours therapies. This activity will take place continuously throughout their life. Purpose: To determine the effect of Therapy Thought Stopping and Family Psychoeducation Toward anxiety clients who undergo hemodialysis in RSAM Bukittinggi. Method: The research design is Quasi Experimental Pre and Post test with a total sample of 64 peoples. Who received Therapy Thought Stopping and Family Psychoeducation as many as 32 peoples, and Therapy Thought Stopping just as much as 32 peoples. The using HARS scale to determine the client's level of anxiety. Results: The results showed a significant decrease in anxiety condition in the intervention group who received Therapy Thought Stopping and family psychoeducation, compared with group who only get of therapy thought stopping (P value <0.05). Conclusion: Therapy Thought Stopping and Family Psychoeducation hemodialysis is recommended to clients who experience anxiety.